ARCHITECTURAL AND STRUCTURAL DESIGN TO COMPARE THE EFFECT OF BLAST LOAD ON IRREGULAR BUILDINGS FROM VIEW POINT STEEL BRACES - Kadhum, Ali Kifah; Kadhum, Lina K. (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims at a study comparing the effect of high load on two types of structural design for a residential building, the first type is with steel frame and the second type with steel braces. each building is composed of 12 floors of different weight of TNT material. This type of loading should now be taken into account in Iraq, especially after the terrorist attack from the bombings that the country is going through from 2003 to the present day. Explosions must be studied in Iraq to avoid significant losses in lives and human and economic equipment. The same multi-frame building is designed with a steel frame with three different weights of TNT 100,350 and 750 kg in order to discuss the difference between the two types of structures in terms of analysis of drift, displacement and shear story and base shear. An ETABS2018 commercial package was used to analyze this 36-meter-high building. The building was analyzed according to the American code, while it was designed according to AISC 360-10 (LRFD) and the U.S. Department of Defense TM5-1300 to carry the explosion. the maximum increase drift it was seen on the 3rdand6th storeys amount 393%,358% for weight 100 kg and same story 392%,363% for weight 350 kg and the maximum increase drift on the 2nd,3rd storeys amount 426%,329% for weight 750 kg TNT. the maximum increased story shear by about 257 % of blast load 100 kg-350, and the maximum increase story shear it was seen in the amount 298% for weight TNT between 350kg-750kg. the maximum increase story shear it was seen in the amount 747% for weight TNT between 100kg-750kg. the maximum increase displacement it was seen on the 6th and 7th storeys amount 360%,357%for weight 100 kg and 350 kg and the maximum displacement increase on the 2nd,3rd storeys amount 438%,393% for weight 750 kg TNT.